Water Footprint of Sugarcane Cultivation in Heavy Metals Contaminated Area, Mae Sot District, Tak Province - Nattawut Sareein (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study was aimed to assess water footprint of sugarcane cultivation in Mae Sot District, Tak Province, Thailand and to investigate heavy metal uptake from soil to sugarcane in contaminated areas. The water footprint is an indicator of freshwater usage, including both direct and indirect uses of water by producer in one production process. It is expressed as water volume per unit of mass (m3/ton). The CROPWAT 8.0 modeling program was used to calculate, using the primary data of cultivation provided from sugarcane fields and bioethanol factory in study sitebetween the years 2011 to 2012. Moreover,Spearman’s correlation coefficient was used to ascribe correlation of climate data, evapotranspiration, precipitation and crop co-efficiency. The results indicated that the blue water footprint which consumed along the supply chain by processing was zero according to no irrigation series. The green water footprint was 98 m3/ton that was referred to the rainwater using as evapotranspiration during crop growth. Furthermore, grey water footprint was 38 m3/tonwhich represented freshwater’s volume required to dilute pollutants based on ambient water quality standards. The total water footprint was 136m3/ton, which was different from previous studies. Beside, high humidity in rainy season leads to reduce referent evapotranspiration. Moreover, crop coefficient was significant positive correlation with referent evapotranspiration that depended on growing period as somewhat low at the beginning of cultivation and rapidly increase in dry season. In addition, the correlation of various factors that affect water footprint directly should be awareness for improving water footprint. In conclusion, the result of this study was from the primary data of local meteorological station and direct interview from farmer. Therefore, water footprint is more exact and different from other previous studies. In order to find out Cd cycle from soil to sugarcane, two sampling sites (control and contaminated areas) were selected from sugarcane plantation in Mae Sot District. Samplings were carried out in wet (August 2011) and dry seasons (February 2012; maturation and ripening phase). Sugarcane roots were collected and cut to the length of 5-10 cms from the base of sugarcane stem. Soil samples were collected at 10-20 cms depth from ground. They were pre-treated and digested by high purity concentrated nitric acid in double layers Teflon digestion vessel and analyzed for heavy metal by ICP-OES. Ca, Fe and Mg were main elementsfound in soil and sugarcane root. For soil samples in contaminated site, Cd concentration was no significantly different between seasons. However it was significantly different between contaminated site and control site. For sugarcane root samples in contaminated site, Cd concentrationwas no significantly different between 1st and 3rdyear of sugarcane. However, season factor was affected to Cd absorption which indicatesthat Cd concentration was significantly different between August and February (6.6 mg/kg and 3.3 mg/kg, respectively). Clearly in dry season the Cd uptake rate was lower than the growth rate. In conclusion, Cd concentration in plant was found because it was cultivated in Cd contaminated area. Furthermore, also found Cd contamination in soil because of anthropogenic such as mining and fertilization.